Hubungan Antara Rasa Syukur Dengan Kesejahteraan Psikologis Pada Mahasiswa Yang Kuliah Sambil Bekerja Part-Time - anjani, wina; Ulpa, Eska Prawisudawati; Rasidin, Yusafrida (ANFUSINA: Journal of Psychology, 2020)
Human life can never be separated from the condition of psychological well-being. Every human being strives to create a prosperous life, both in physical, social, and mental conditions so that the quality of his life increases. One of the factors that influence psychological well-being is gratitude. This is because gratitude is able to create a positive outlook on events that occur in life. This study aims to determine the relationship between gratitude and psychological well-being in students who workin college part-time. The hypothesis proposed in this study is that there is a relationship between gratitude and psychological well-being in students who study part-time work. The subjects of this research are students who study part-time at the Ushuluddin faculty and theUIN Raden Intan Lampung religious studies class 2017totaling 70 students. Thetechnique used atechnique samplingtotal sampling.   The data collection technique used a gratitude scale of 19 items (ɑ = 0.865) and a psychological well-being scale of 21 items (ɑ = 0.868).The results of the study indicate a relationship between gratitude and psychological well-being in students who workcollege part-time in. The data analysis used was the Pearson product moment correlation. The results showed that the two variables had a significant relationship. rxy = 0.510 with p = 0.000 (p <0.01), this indicates that there is a significant positive relationship between gratitude and psychological well-being in students who studywhile working  part-time  so that the hypothesis is accepted. The higher the gratitude, the higher the resulting psychological well-being. The effective contribution of 26% is influenced by the independent variables in this study and 74% is influenced by other factors.